Valproic Acid Attenuates Oxidative Damage in Rat Spleen Tissue Induced By Spinal Cord Damage - Ulaş, Mustafa (My University, 2022)
Events such as oxidative stress caused by spinal cord injury (SCI) are a serious condition because they negatively affect many organs. Alternative treatment options for this type of injury are quite limited. In this study, we planned to investigate the effect of oxidative damage on the spleen tissue of rats with spinal cord damage and the protective role of valproic acid (VPA) in this damage. Sixteen Wistar albino rats were divided into two equal groups. No treatment was administered to the rats in Group 1 (SCI-(Control), but a single dose of 300 mg/kg intraperitoneally VPA was administered to the rats in Group 2 (SCI-VPA). Superoxide dismutase (SOD) activities, total antioxidant status (TAS) and total oxidant status (TOS) levels were examined as markers of oxidative stress in spleen tissues taken after decapitation of rats. VPA treatment increased the SOD and TAS level but decreased the TOS level, indicating improved oxidative damage and impaired enzymatic antioxidant levels in spleen tissue homogenate damaged by SCI. We have observed that VPA, which has many beneficial properties, has a significant healing effect on spleen tissue affected by SCI-induced oxidative stress.
Keywords: Biyoloji; Farmakoloji ve Eczacılık